Gender Differences in Substance Use Across Marital Statuses - Blair, Sampson; Menasco, Melissa A. (International Journal of Criminology and Sociology, 2016)
Previous studies have noted that the relationship status of adults is substantially linked with levels of substance use. Understandably, the marital status of adults continues well beyond its initial phases, sometimes resulting in divorce, separation, or remarriage. This study seeks to extend our understanding of the linkages between marital status and substance use among adults. Using data from the 2012 National Survey on Drug Use and Health, we examine the substance use levels among a nationally representative sample of 14,715 adults. The analyses indicate that, for both females and males, marriage is, indeed, associated with lower levels of alcohol, cigarette, and marijuana use. Divorced individuals reported the highest levels of substance use. Interestingly, remarried individuals report higher levels of substance use than their counterparts in their first marriage, yet remarried men and women report lower levels of usage than do those who are currently divorced. Contextual and individual characteristics also yield several interesting patterns. In particular, distress and depression are shown to be much stronger predictors of substance use levels among divorced and remarried individuals. Divorced and remarried women, as compared to their male counterparts, are shown to be significantly more influenced by their employment status. The implications of this study are discussed, as are the potentially reciprocal nature of marital status and substance use.